Karakteristik Sensori Tepung Jewawut dengan Perendaman Anti-browning Agent - Islamiyah, Syahmidarni Al; Samang, Andi Marlisa Bossa; Nurhafnita, Nurhafnita; Tiffany, Margaretha Hanna (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2024)
The purpose of this study was to determine the sensory properties of jewawut flour by soaking citric acid as an anti-browning agent. The study was an experimental study using a two-factorial Complete Randomized Design three repeats. The variables of the study were concentration (A) consisting of 1.5% (A1), 2% (A2), 2.5% (A3) and soaking duration (B), and soaking duration (B) consisting of 30 minutes (B1), 45 minutes (B2), and 60 minutes (B3). Data collection through observation and measurement of sensory parameters including color, aroma, and texture using the hedonic method. The results showed that the sensory properties of jewawut flour with citric acid soaking both color, texture, and aroma were favored by the panelists, which were on a scale of 4 (likes). The color of the white jewawut flour is slightly yellowish, the texture is very soft (mesh size 60), and the distinctive aroma that remains smelled. The addition of citric acid as an inhibitor of the browning reaction has an effect by producing a brighter flour color as the concentration increases (1.5-2.5%), the texture also gets softer. However, in terms of aroma, the addition of citric acid with a high concentration will affect the aroma of flour to sour.